Bright Soliton and Bright–Dark Soliton Pair in an Er-Doped Fiber Laser Mode-Locked Based on In2Se3 Saturable Absorber - Wei, Qin; Han, Xile; Zhang, Huanian; Li, Chonghui; Zhang, Chao; Man, Baoyuan (Frontiers in Physics, 2021)
The output power in ultrafast fiber lasers is usually limited by the absence of a desirable real saturable absorber (SA) with high damage threshold and large modulation depth. In this work, the output energy of Erbium-doped fiber laser (EDFL) was greatly improved by employing a double-end pumped ring laser cavity and a saturable absorber (SA) with high threshold and large modulation depth. In2Se3 nanoflakes were successfully prepared by using the physical vapor deposited (PVD) method. Based on the PVD-In2Se3 SA, stable mode-locked bright pulses and triple-wavelength dark-bright pulse pair generation were obtained successfully by adjusting the polarization state. The average output power/pulse energy were 172.4 mW/101 nJ and 171.3 mW/100 nJ, which are significantly improved compared with the previous work. These data demonstrate that the proposed PVD-In2Se3 can act as a promising highly-nonlinear photonic material for high-power fiber laser.